Vaccine safety - is the SARS-CoV-2 vaccine any different? - Noam Tau; Dafna Yahav; Daniel Shepshelovich (Taylor & Francis Group, 2021)
Vaccines have changed modern medicine, and are a mainstay in reducing morbidity and mortality from infections. Our research group recently published a study in which we found that vaccines approved by the US Food and Drugs Administration were safe with few clinically important post-approval adverse effects. The current COVID-19 pandemic presents regulators with the unprecedented challenge of balancing a public demand for the rapid development and approval of a safe and effective SARS-CoV-2 vaccine without compromising the strict pre-marketing requirements used for previous vaccines. Here, we review the approval process and safety profiles of FDA approved vaccines and discuss some of the challenges currently facing the FDA regarding the SARS-CoV-2 vaccine approval.